An introduction to the philosophy of mind - Lowe, E J (Cambridge University, 2013)
Using a problem-centred approach designed to stimulate as well as instruct, the author of this text begins with a general examination of the mind-body problem and moves on to detailed examination of more specific philosophical issues.